2021
DOI: 10.2109/jcersj2.21066
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sintering of 3 mol % Y<sub>2</sub>O<sub>3</sub>-doped ZrO<sub>2</sub> by a combined rapid furnace heating and shrinkage-controlled flash sintering protocol

Abstract: Flash sintering has attracted much attention as a useful sintering technique that is able to lower the sintering furnace temperature and shorten the sintering time. To further improve this original flash sintering technique, we have developed a technique to facilitate shrinkage at a constant shrinkage rate by controlling the power dissipation during a flash state, which is termed as shrinkage-controlled flash (SCF) sintering. Here, we combine this SCF sintering method with a rapid furnace heating process to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…The same question can be launched at UHS. Indeed the influence of heating rate on sintering has been of interest for a long time, 14,15 although the experiment with graphite sheet heaters for ultrafast heating represents a new development. 16 Indeed, the first application of flash and UHS into products can be traced back to two inventions at the late nineteenth century.…”
Section: Introductionmentioning
confidence: 99%
“…The same question can be launched at UHS. Indeed the influence of heating rate on sintering has been of interest for a long time, 14,15 although the experiment with graphite sheet heaters for ultrafast heating represents a new development. 16 Indeed, the first application of flash and UHS into products can be traced back to two inventions at the late nineteenth century.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, SCF-sintering protocol is one of the most useful techniques that no shell-like structure is formed and a green compact is densified uniformly, in which the electric current is controlled without the occurrence of a steep power spike. 14),24), 25) In summary, we investigated the cross-sectional microstructure of 8YSZ compact prepared by conventional flash sintering under AC electric field, which exhibits a phenomenon of restricted densification. It was found that a densified portion with a thickness of about 25 ¯m was formed at the periphery of the porous sintered compact with lower density, which is shell-like structure covering a whole of the sintered compact.…”
mentioning
confidence: 99%
“…Different sintering methods can significantly affect the fracture toughness and mechanical properties of ZrO 2 ceramics. [70][71][72][73] Therefore, it is crucial to select suitable sintering methods according to different application scenarios. [74][75][76] Figure 5 shows the schematics of several common sintering methods.…”
Section: Effects Of Sintering Methods On Fracture Toughnessmentioning
confidence: 99%